Приобретение права собственности на бесхозяйные вещи - Shebetnikova, Yekaterina (Europejskie Stowarzyszenie Studentów Prawa ELSA Poznań, 2014)
The study aims at an evaluation of the acquisition of the ownership of the unclaimed property. The author present this form of the acquisition of the right to property in the Russian Civil Code emphasising the necessity of fulfilling law norms.
The acquisition of property right of unclaimed property
Keywords: acquisition of property right unclaimed property; civil law